2017
DOI: 10.1177/0042098017741262
|View full text |Cite
|
Sign up to set email alerts
|

Residential choices of foreign highly skilled workers in the Netherlands and the role of neighbourhood and urban regional characteristics

Abstract: In the international competition for talent, local and national policy makers are keen to better understand the location choices of highly skilled workers in order to design more effective policies geared towards the group's attraction and retention. In this study, we explain whether and to what extent the local living environment, in particular characteristics at the neighbourhood and urban regional level, affect the residential choices of foreign highly skilled workers. We make use of register data from Stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…In terms of selectivity, it is important to not only account for the spatial socioeconomic conditions because negative effects of neighbourhood deprivation might be confounded with immigrant group effects. In particular, a high concentration of coethnics in the neighbourhood can become relevant for the labour market and educational prospects of immigrant youths (Beckers & Boschman, 2017; Wang & Ramsden, 2018; Zorlu & Mulder, 2011; Zuccotti & Platt, 2017). Individuals of similar immigrant background are more likely to interact and form social ties (Giulietti et al, 2013; Granovetter, 1973; Nieuwenhuis et al, 2015; Putnam, 2000).…”
Section: Theoretical Argumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of selectivity, it is important to not only account for the spatial socioeconomic conditions because negative effects of neighbourhood deprivation might be confounded with immigrant group effects. In particular, a high concentration of coethnics in the neighbourhood can become relevant for the labour market and educational prospects of immigrant youths (Beckers & Boschman, 2017; Wang & Ramsden, 2018; Zorlu & Mulder, 2011; Zuccotti & Platt, 2017). Individuals of similar immigrant background are more likely to interact and form social ties (Giulietti et al, 2013; Granovetter, 1973; Nieuwenhuis et al, 2015; Putnam, 2000).…”
Section: Theoretical Argumentsmentioning
confidence: 99%
“…Immigrants are known to be not evenly distributed across residential areas. Factors such as economic conditions and the presence of coethnics influence the place of residence of immigrants (Beckers & Boschman, 2017; Viñuela, Gutiérrez Posada, & Rubiera Morollón, 2019; Wang & Ramsden, 2018; Zorlu & Mulder, 2011). This concentration in residential areas suggests that spatial contexts are particularly important for ethnic minorities' employment prospects.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics and factors influencing residential location choice vary among different demographics [2]. The highly educated population, which forms a city's valuable human resource and the basis for its innovative and sustainable development, has become the target of contention for various cities [3,4]. Therefore, an in-depth understanding of the characteristics and mechanisms of the highly educated population's choice of residential location not only helps in attracting talents, but also provides an important reference point for improving the competitiveness and sustainable development of cities.…”
Section: Introductionmentioning
confidence: 99%
“…The highly educated population, with a higher income and more elevated social status, show greater need for landscape and environment. Studies have found that landscape and environment exert a significant impact on the housing choices of highly educated people [3], which warrants the study of such factors. From the perspective of human needs, the choice of residential location tends to be based on convenience first, and then on landscape and environment, which serve to satisfy higher-level living needs.…”
Section: Introductionmentioning
confidence: 99%
“…With the rise of the consumer city (Glaeser et al, 2001;Glaeser and Gottlieb, 2006), people are drawn to cities for their diverse and dense array of amenities. In cities people migrate to areas with attractive amenities (Zheng, 2016), including restaurants (Beckers and Boschman, 2017). Restaurants are an important amenity, and residents not only value the quantity of restaurants but also the ratings of restaurants (Kuang, 2017…”
Section: Conclusion and Future Researchmentioning
confidence: 99%